microRNAs in breast cancer: regulatory roles governing the hallmarks of cancer - Goh, J.; Loo, S.; Datta, A.; Siveen, K.; Yap, W.; Cai, W.; Shin, E.; Wang, C.; Kim, J.; Chan, M.; Dharmarajan, Arunasalam; Lee, A.; et al. (Blackwell Publishing Ltd, 2015)
A large number of etiological factors and the complexity of breast cancers present challenges for prevention and treatment. Recently, the emergence of microRNAs (miRNAs) as cancer biomarkers has added an extra dimension to the ‘molecular signatures’ of breast cancer. Bioinformatic analyses indicate that each miRNA can regulate hundreds of target genes and could serve functionally as ‘oncogenes’ or ‘tumour suppressor’ genes, and co-ordinate multiple cellular processes relevant to cancer progression. A number of studies have shown that miRNAs play important roles in breast tumorigenesis, metastasis, proliferation and differentiation of breast cancer cells. This review provides a comprehensive overview of miRNAs with established functional relevance in breast cancer, their established target genes and resulting cellular phenotype. The role and application of circulating miRNAs in breast cancer is also discussed. Furthermore, we summarize the role of miRNAs in the hallmarks of breast cancer, as well as the possibility of using miRNAs as potential biomarkers for detection of breast cancer.